PSYCHOLOGICAL DISTRESS AS A CORRELATE OF LEARNING DISPOSITION DURING COVID-19 PANDEMIC AMONG UNDERGRADUATES OF OLABISI ONABANJO UNIVERSITY, AGO IWOYE, OGUN STATE - Iheanyichukwu, Temidayo; Babalola, Segun Oyetunde; Iheanyichukwu, Benjamin Franklin; Falade, Enitan Omolara; Ekeh , Agustina Ngozi (African Journal of Behavioural and Scale Development Research, 2022)
This study sought to establish the relationship between psychological distress and the learning disposition of undergraduates of Olabisi Onabanjo University, Ago-Iwoye during the COVID-19 pandemic. It hypothesized that there would be no significant relationship between psychological distress and the learning disposition of undergraduate students. The survey research design was adopted using two standardized instruments (Psychological distress scale and learning styles scale) in the collecting of data. 400 participants were randomly selected among undergraduates in the faculty of Education of Olabisi Onabanjo University. Simple linear correlation was used to analyze the data collected at 0.05 level of significance. Result indicated there is no significant relationship between psychological distress and learning styles of undergraduates during COVID-19 pandemic.